ASĀSIYYĀTU TARBIYYAT AL-ʻULŪM AL-LADUNIYYAH FĪ AL-TAFSĪR - Cato; Kahfi, Muhammad Alim (STAI AL-ANWAR SARANG, 2021)
Laduni science is an extraordinary event that can be said to be beyond human behavior and this can be proof that Allah knows everything. In addition, it is also a reminder for us that even though humans have intelligence, they still cannot reveal all the secrets of God Almighty. Actually there is no definite theory to arrive at knowledge of laduni science, because it depends entirely on who will provide knowledge about the science. In contrast to science which is included in the category of exact knowledge, it is largely determined by one's perseverance. The more diligent and diligent in learning, the smarter and gain a lot of knowledge. And we will discuss in this article the basics of laduni science education in the interpretation of the Qur'an. Among them are verses and hadiths that discuss laduni science and comments by Sufis about laduni education.